Highly polarized emission from organic single-crystal light-emitting devices with a polarization ratio of 176 - An, Ming-Hui; Ding, Ran; Zhang, Xu-Lin; Chen, Shuo-Nan; Wang, Ya-Nan; Ye, Gao-Da; Zhu, Qin-Cheng; Chen, Nian-Ke; Liu, Yu; Feng, Jing; Sun, Hong-Bo (Optica, 2022)
Polarized light emission from organic light-emitting devices (OLEDs) is of considerable current interest because of their great potential in various optical and optoelectronic devices. Utilizing materials with aligned molecular orientation is a simple and promising way to realize highly polarized OLEDs; however, both the polarization ratio and efficiency are still far from the requirements for practical applications. Organic single crystals with inherent anisotropic properties induced by their long-range periodic order are ideal candidates for intrinsically polarized emission. Herein, the intrinsic polarization has been dramatically amplified by constructing a microcavity structure in organic single-crystal OLEDs to effectively couple microcavity resonance to polarized light. A high polarization ratio of 176 has been achieved from the polarized OLEDs. Moreover, highly aligned single-crystalline molecules with small tilted orientation angles to the crystal surface result in a high outcoupling efficiency for surface-emitting crystal OLEDs. A maximum luminance of 6122 c d / m 2 and current efficiency of 1.86 cd/A were achieved, which are among the best performances for crystal OLEDs. This work may lead to a new strategy for simultaneously enhancing the polarization ratio and efficiency of polarized OLEDs and promote their development in various optical and optoelectronic applications.